2005
DOI: 10.1254/jphs.cp0040014
|View full text |Cite
|
Sign up to set email alerts
|

Drug Dependence, Synaptic Plasticity, and Tissue Plasminogen Activator

Abstract: Abstract. The mesocorticolimbic dopaminergic system plays an important role in the reinforcing effects of drugs of abuse, and the activity-dependent synaptic plasticity of the system is involved in drug dependence. A DNA microarray screening revealed that the expression levels of tissue plasminogen activator (tPA) mRNA in the nucleus accumbens of morphine-or methamphetamine-dependent rats were significantly increased compared with those in control animals. Since tPA plays a role in synaptic plasticity, we hypo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
35
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 33 publications
4
35
0
Order By: Relevance
“…These cocaine-induced behavioral changes, associated with uPA expression, could be suppressed in the presence of doxycycline or of siRNA targeted against uPA [18,19]. Collectively, these and other data [13] strongly support a major role for urokinase in psychostimulant-mediated plasticity changes.…”
Section: Introductionsupporting
confidence: 55%
See 2 more Smart Citations
“…These cocaine-induced behavioral changes, associated with uPA expression, could be suppressed in the presence of doxycycline or of siRNA targeted against uPA [18,19]. Collectively, these and other data [13] strongly support a major role for urokinase in psychostimulant-mediated plasticity changes.…”
Section: Introductionsupporting
confidence: 55%
“…The present study firmly consolidates these data and points to an important role of the plasmin system in chronic cocaine. Other studies have shown that the plasmin system releases dopamine in the NAc upon psychostimulants, which activates long-term synaptic plasticity and remodeling, and acutely participates in the rewarding effects of drugs such as methamphetamine or morphine [13,14,16,17,69]. It has been shown that tPA regulates nicotine-induced reward and dopamine release through protease activated receptor-1 [70].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present findings are consistent with the view that tPA activator plays a key role in neuroplasticity and is a neuromodulator in the CNS (Yamada et al, 2005). Moreover, as previously mentioned, the tPA-plasmin system is involved in the rewarding effects of drugs of abuse (eg, morphine), possibly through regulation of dopamine release in the NAc (Nagai et al, 2004Ito et al, 2006Ito et al, , 2007Yan et al, 2007).…”
Section: Discussionsupporting
confidence: 93%
“…In the brain parenchyma, tPA is involved in physiological processes, including synaptic plasticity (Huang et al, 1996;Calabresi et al, 2000;Zhuo et al, 2000;Mataga et al, 2002;Pang et al, 2004) and behaviors (Seeds et al, 1995(Seeds et al, , 2003Madani et al, 1999;Pawlak et al, 2002Pawlak et al, , 2003Matys et al, 2004;Yamada et al, 2005). tPA also displays important roles in models of acute and chronic brain disorders, such as ischemic brain injury, seizure, and multiple sclerosis (Tsirka et al, 1995;Chen and Strickland 1997;Wang et al, 1998;Wu et al, 2000;Gveric et al, 2001;Lu et al, 2002;Liot et al, 2006).…”
Section: Introductionmentioning
confidence: 99%